1999
DOI: 10.1016/s0960-9822(00)80052-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sonic hedgehog signaling in vivo results in craniofacial neural crest cell death

Abstract: Reduction of Shh signaling after neural tube closure resulted in a transient decrease in neural tube cell proliferation and an extensive increase in cell death in the neural tube and neural crest, which in turn resulted in decreased head size. The phenotypes observed after reduction of Shh are similar to those observed after cranial neural crest ablation. Thus, our results demonstrate a role for Shh in coordinating the proliferation and survival of cells of the neural tube and cranial neural crest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
210
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(222 citation statements)
references
References 37 publications
9
210
1
2
Order By: Relevance
“…Moreover, the cyclin-dependent kinase inhibitor p27, a promoter of cell-cycle arrest and differentiation, has been reported to also have a proapoptotic function (Wang et al, 1997; for review, see PhilippStaheli et al, 2001;Coqueret, 2003). A role for Shh signaling in controlling cell-death events has also been suggested by the widespread apoptosis observed in neural progenitors after inhibition of Shh activity (Ahlgren and Bronner-Fraser, 1999;Charrier et al, 2001) and by the ability of the Hedgehog receptor Patched to trigger apoptosis in the absence of Shh signal (Thibert et al, 2003). Whether REN-induced apoptosis is related to its ability to regulate both p27 and Hedgehog signaling needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cyclin-dependent kinase inhibitor p27, a promoter of cell-cycle arrest and differentiation, has been reported to also have a proapoptotic function (Wang et al, 1997; for review, see PhilippStaheli et al, 2001;Coqueret, 2003). A role for Shh signaling in controlling cell-death events has also been suggested by the widespread apoptosis observed in neural progenitors after inhibition of Shh activity (Ahlgren and Bronner-Fraser, 1999;Charrier et al, 2001) and by the ability of the Hedgehog receptor Patched to trigger apoptosis in the absence of Shh signal (Thibert et al, 2003). Whether REN-induced apoptosis is related to its ability to regulate both p27 and Hedgehog signaling needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that Hh signaling can regulate growth and survival in both differentiated and undifferentiated cells (47)(48)(49) and can also regulate lineage-specific differentiation (50)(51)(52). Hh family members tend to act in a paracrine fashion (12).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a targeted null mutation in Shh caused severe cranial deficiencies that initially precluded direct assessment of the role of Shh in facial morphogenesis (Chiang et al, 1996), inhibition of Shh signaling in the outgrowing chick frontonasal process with a function blocking antibody inhibited facial outgrowth and caused cleft lip (Hu and Helms, 1999). Ahlgren and Bronner-Fraser (1999) showed that inhibition of Shh in the cranial mesenchyme also caused neural crest mesenchymal cell death. Moreover, Ahlgren et al (2002) demonstrated that application of Shh protein rescued cranial mesenchymal death in chick embryos induced by ethanol treatment.…”
Section: The Shh Pathwaymentioning
confidence: 99%